Lesson study learning community melalui model transcript based learning analysis (TBLA) dalam pembelajaran IPA - Eko Susetyarini; Sri Wahyuni; Roimil Latifa (JINoP (Jurnal Inovasi Pembelajaran), 2021)
Lesson study builds a learning community among teachers, students, academics, and education observers. Transcript Based Learning Analysis (TBLA) model is among the models used to analyze learning transcripts more thoroughly. This study aims to describe the patterns of lesson study in science learning through TBLA analysis. Descriptive qualitative approach was employed to describe these phenomena. The study site was SMP Muhammadiyah 8 Batu. The subjects were 8th graders studying about Plant Tissue; through plan, do, see cycle. The research instruments were video and audio recorders, and field notes. The data collection is carried out through documentation, observation and discussion. The collected data was in the forms of transcripts of Lesson Study. The data was analyzed through the TBLA analysis model. Results describe the conversations between teachers and students, in which 43 teacher-student conversations with linear patterned learning were categorized as Student Center Learning. It is implied that in learning about plant tissue, linear pattern communication helped students to achieve learning objectives as they underwent student-centered learning. Results of this study suggest a reference for reflection in teacher professional learning to carry out effective learning.